Green Human Resource Management Approach: Implementation for Development Team and Organization (Mini Review) - Supardi; Yayan Hendayana; Dedy Kurniawan Nasution (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this scientific article is to prove between three variables from existing scientific articles about the variables in this study qualitatively by using a literature review, the research method used is qualitative by searching literature reviews from scientific articles from various reputable international journals Result discussion above answers everything presented by researchers in this scientific article, with a qualitative result that exists. The recommendations in this study provide a differentiating variable that is considered a research gap and can be used for other researchers with different objects such as differentiators Green Recruitment & Selection, Green Training, Involment, and Development, Green Performance & Compensation, Green Perfoamnce Management And Appraisal, Green Employee Involment Practices, Top Management, Environmental Oriental, Green Team Creativity and Organizational Sustainability, green culture, green OCB, green Values, Commiment HRM, Environmental Regulation, Green Creativity, Green Team Creativity and Technological Turbulence, sustainability performance, and emerging economy